Influence of forest fires on the formation processes of low molecular weight dicarboxylic acids, ω-oxocarboxylic acids, pyruvic acid and α-dicarbonyls in springtime fine (PM2.5) aerosols over Southeast Asia. (1st February 2021) - Boreddy, Suresh K.R.; Parvin, Fahmida; Kawamura, Kimitaka; Zhu, Chunmao; Lee, Chung-Te
Abstract: The present study reports on homologous series of dicarboxylic acids (C2 –C12 ), ω-oxocarboxylic acids (ωC2 -ωC9 ), pyruvic acid, and α-dicarbonyls (glyoxal and methylglyoxal) in near source biomass burning influenced (PM2.5 ) aerosols collected at Doi Ang Khang (DAK), Thailand, during an intense forest fire (March 1 to April 13, 2015) occurred in the vicinity of the sampling site over Southeast Asia (SEA). The molecular distributions of diacids were characterized by a predominance of oxalic (C2 ) acid followed by succinic (C4 ) and malonic (C3 ) acids. The abundance of maleic acid (M) was almost three times higher than that of fumaric acid (F). The observed lower values of C3 /C4 (mean: 0.54), C2 /C4 (4.45) and F/M ratios (0.33), indicating the limited photochemistry of organic aerosols at DAK and these ratios were comparable to those reported for biomass burning influenced aerosols (C3 /C4 : 0.51–0.66, C2 /C4 : 4.0, and F/M: 0.2–0.35). Further, strong positive correlations (R 2 > 0.80) were observed for diacids and related organic compounds with levoglucosan (LG, a unique tracer for biomass burning emission), suggesting that enhanced biomass burning associated with forest fires are major sources of diacids at DAK. This inference was further supported by the air mass back trajectories and MODIS (moderate resolution imaging spectroradiometer) derived fire spots over the study region. The formation pathway of C2 was largely linked to biomass burning derived precursor compounds as inferred from the correlation coefficient matrix analysis. We also found that C3 /C4 and C2 /C4 ratios were negatively correlated with LG, although they have strongly correlated each other. This inference suggests that biomass burning affect not only the concentration levels of organic aerosols but also their formation processes in the atmosphere. The present study demonstrates that intensive biomass burning during forest fires in SEA largely control the levels of carbonaceous aerosols and seriously affect the climate in the outflow regions. Graphical abstract: Image 1 Highlights: Near source PM2.5 particles collected during an intense forest fire at DAK, Thailand. C2 is the most abundant organic acid, followed by C4, C3 and Ph. Maleic acid (M) was almost three times higher than that of fumaric acid (F). C3 /C4 and F/M ratios were comparable to those fresh biomass burning aerosols. C3 /C4 and C2 /C4 ratios have increased significantly with decrease in levoglucosan.